Effects of a Character Strengths Intervention on Emerging Adults’ Identity Formation, Self-Efficacy, and Self-Doubt - Wong, Wen Pin; Pheh, Kai-Shuen; Tan, Chee Seng (UI Scholars Hub, 2024)
This study aimed to determine the effects of a single-session character strength intervention (CSI) on enhancing identity formation and self-efficacy and decreasing self-doubt of Malaysian emerging adults enrolled in tertiary education. A randomized active-controlled trial with a pretest, a posttest, and a 2-week follow-up was performed. A total of 129 undergraduate students (aged 18–25) were randomly assigned to either the CSI or the control group, who participated in a gatekeeper training for suicide prevention. Data from emerging and perceived adults were analyzed separately through a mixed-design analysis of variance. CSI showed no effects on improving emerging adults’ identity formation, self-efficacy, and self-doubt. In addition, this study investigated incidental findings such as the developmental differences between emerging and perceived adults at pretest, in which emerging adults had significantly lower identity formation and self-efficacy, as well as significantly higher self-doubt, than perceived adults. Although the current results are insignificant, this study revealed important developmental differences between emerging and perceived adults.